HUBUNGAN KARAKTERISTIK PERAWAT DENGAN PEMAHAMAN PENERAPAN RESUSITASI JANTUNG PARU (RJP) DI RUANGAN IGD DAN ICU RSUD DR. ACHMAD MOCHTAR BUKITTINGGI TAHUN 2017 - Aldo Yuliano; Misye Herlindawati; Ida Suryati (JURNAL KESEHATAN PERINTIS, 2018)
Cases of coronary heart disease are increasing in developed and developing countries and it is estimated that by 2020 cases of coronary heart disease have reached 82 million cases. More than 60% of coronary heart disease burden globally occurs in developing countries. The purpose of this study was to determine the relationship Understanding Application Characteristics Nurse With Cardiac Pulmonary Resuscitation (CPR) in the ER and ICU hospital room Dr.Achmad Mochtar Bukittinggi Year 2017. This research method used descriptive analytic study designs Correlation approach, then the data is processed by using Chi Square test. The sample in this study as many as 33 people responden. Obtained statistical test p value = 0.014 (p <α), it can be concluded the Relationship Age Nurse With Application Understanding Cardiac Pulmonary Resuscitation (CPR), the value of p value = 0.003 (p <α ), It can be concluded that there is a relationship of Nurses education with the understanding of Implementation of Pulmonary Heart Resuscitation (RJP), obtained p value = 0,031 (p <α) it can be concluded the existence of work relationship Nurses With Understanding Implementation of Pulmonary Heart Resuscitation (RJP) value = 0.010 (p <α), it can be concluded their tenure gender relations nurse With Application understanding Cardiac Pulmonary Resuscitation (CPR). Suggestion in this research is The result of this research can be picture in improving health service especially in application of Lung Heart Resuscitation (RJP).